The Status of Masked Bobwhite Recovery in the United States and Mexico - William P. Kuvlesky Jr.; Sally A. Gall; Steve J. Dobrott; Susan Tolley; Fred S. Guthery; Stephen A. DeStefano; Nina King (National Quail Symposium Proceedings, 2017)
The masked bobwhite (Colinus virginianus ridgwayi) is an endangered species currently numbering <1500 individuals and restricted to 2 locales in southeastern Arizona and northcentral Sonora, Mexico. The subspecies' endangered status is attributed to overgrazing of Sonora savanna grassland that began during the late 1880's and continued well into the 20th century. This overgrazing resulted in the conversion of many native grass pastures to the exotic bufflegrass (Cenchrus ciliaris). The Arizona masked bobwhite population was extirpated around the turn of the century, and the Sonoran population was thought to have disappeared during the 1940's until a small remnant population was discovered on a ranch near Benjamin Hill, Sonora , in 1964 . Masked bobwhite recovery efforts have a dynamic, long history of nearly six decades. Current masked bobwhite recovery efforts focus on reestablishing a self-sustaining population on the Buenos Aires National Wildlife Refuge (BANWR) in the United States, as well as 2 remnant wild populations located on privately owned ranches in northcentral Sonora.